Guinea : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper focuses on Ex Post Assessment of Longer-Term Program Engagement for Guinea. Guinea's stabilization and reform efforts have been almost continuously supported by IMF financial arrangements since 1987. The paper reviews developments under the last two IMF-supported programs during 1997-2004. It highlights that Guinea's performance under these programs has been disappointing. The paper discusses program objectives, policies, and performance and reflects on lessons learned and the remaining challenges. It also presents a discussion on possible future relations between the IMF and Guinea.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet